Funerary practices in the 1990s - Gustafsson, Göran (University3, 2013)
Already at the planning stage of the “Funerary Practices – A Study of Social Differences after Death” project, the fundamental idea was that the main data for the study would be provided by a broad survey of the large majority of all Church of Sweden funerals. It is well-known that the weakening of Christian customs related to service attendance and the use of other Christian practices (baptism, confirmation, and church weddings) is less pronounced when it comes to church funerals.
The ritual form of the church funeral is largely defined through the order of service for funerals in Den svenska kyrkohandboken [approx. The Swedish Church Manual]. However, for several points in the service, the handbook offers alternative forms and the possibility of leaving them out, and the final part of the service mainly depends on whether there will be an earth burial or a cremation. There is hardly any information from previous studies regarding the formulation of the funeral service, and there is no individual information about what happens to the coffin with the deceased after the service.
These facts alone are enough to warrant a study of funerary practices and their variations. The section on funerals in the church manual, which defines the ritual framework for funeral services, begins by observing that the funeral is part of a situation extending from the deathbed to the final leave-taking by the grave. A similar view informed the idea of a broad study of contemporary funerary practices in Sweden: not only - or mainly – would the study focus on the rituals of the church or chapel; it would also examine what goes on before and, to some extent, after the funeral service to the largest possible extent. Above all, it would address the social aspects (broadly interpreted) of funerals not regulated by the church manual or otherwise governed by established regulations.

The raw data for the study is available from LUKA, the Church History Archive of Lund University.

Purpose:

During the second and third quarter of 1997 were an extensive survey material concerning funerals collected at the Department of Theology at University of Lund. The collection was part of a research project on "Funeral Customs - the study of social differences after death" conducted with funding from the Social Science Research Council (SFR). The survey forms provide information on many matters concerning funeral customs of modern Sweden. The questions sought to capture both the social events surrounding the funerals as well as the ritual events of the funeral church services.

The dataset is comprised of an SPSS file, containing coded answers to the study's questionnaire.

Redan då projektet "Begravningsseder - studier av sociala skillnader efter döden" började planeras var en grundtanke att en bred enkätundersökning om den stora majoritet av alla begravningar som Svenska kyrkan svarar för skulle utgöra ett huvudmaterial inom projektet. Det är välbekant att den försvagning av den kristna seden som kan iakttas både vad gällande gudstjänstbesök och utnyttjande av de övriga kyrkliga handlingarna (dop, konfirmation och kyrklig vigsel) inte i lika hög grad gjort sig gällande när det gäller de kyrkliga begravningarna.
Den rituella formen för de kyrkliga begravningarna är i stort sett fastlagd i Den svenska kyrkohandbokens ordning för begravningsgudstjänster. Handboken erbjuder emellertid vid flera av momenten i gudstjänsten både alternativa former och möjligheter till utlämnande och vilken avslutning gudstjänsten får sammanhänger främst med om den döda skall jordbegravas eller kremeras. Beträffande begravningsgudstjänsternas utformning finns knappast några uppgifter från tidigare studier och när det gäller vad som efter gudstjänsten sker med kistan med den döda finns det inte några individuella uppgifter.
Bara de nämnda förhållandena kunde motivera en undersökning av hur begravningssederna ter sig i praktiken och vilka variationer som finns. I den kyrkohandbok som anger de rituella ramarna för hur en begravningsgudstjänst skall utformas inleds avsnittet om "Begravning" med ett konstaterande att "Begravningen ingår i ett sammanhang som sträcker sig från dödsbädden till avskedet vid graven". Ett liknande synsätt låg bakom tankarna på en bred undersökning av hur begravningssederna gestaltar sig i dagens Sverige: den skulle inte bara eller främst koncentreras på det rituella skeendet i kyrkan eller gravkapellet utan den skulle också i görligaste mån uppmärksamma vad som händer före och i viss mån också efter begravningsgudstjänsten och den skulle framförallt ta upp de i bred mening sociala aspekterna på en begravning som inte regleras i Kyrkohandboken eller på annat sätt styrs av fastlagda regelverk.

Studiens grundmaterial finns hos LUKA, Lunds kyrkohistoriska arkiv.

Syfte:

Under andra och tredje kvartalet 1997 insamlades vid Teologiska institutionen i Lund ett omfattande enkätmaterial rörande begravningar. Materialinsamlingen ingick som ett led i ett forskningsprojekt om "Begravningsseder - studier av sociala skillnader efter döden" som bedrevs med stöd från Socialvetenskapliga Forskningsrådet (SFR). Enkätformulären ger upplysningar om många förhållanden som rör begravningssederna i dagens Sverige. Frågorna avsåg att fånga såväl det i bred mening sociala skeendet kring begravningarna som det rituella skeendet vid begravningsgudstjänsterna.

Datasetet utgörs av en SPSS-fil med kodade svar på studiens enkät.
Begravningssed på 1990-talet
Keywords: customs and traditions; seder och bruk; funerals; begravningar; rite; rit; Church of Sweden; Svenska kyrkan; Social behaviour and attitudes; Socialt beteende och attityder; Religion and values; Religion och värderingar; Sociology; Sociologi; Philosophy, Ethics and Religion; Filosofi, etik och religion; Religious Studies; Religionsvetenskap; Ethnology; Etnologi